Highly-excited Rydberg excitons in synthetic thin-film cuprous oxide - Jacob DeLange; Kinjol Barua; Anindya Sundar Paul; Hamid Ohadi; Val Zwiller; Stephan Steinhauer; Hadiseh Alaeian (Scientific Reports, 2023)
Abstract Cuprous oxide ( $$\hbox {Cu}{}_2\hbox {O}$$ Cu 2 O ) has recently emerged as a promising material in solid-state quantum technology, specifically for its excitonic Rydberg states characterized by large principal quantum numbers (n). The significant wavefunction size of these highly-excited states (proportional to $$n^2$$ n 2 ) enables strong long-range dipole-dipole (proportional to $$n^4$$ n 4 ) and van der Waals interactions (proportional to $$n^{11}$$ n 11 ). Currently, the highest-lying Rydberg states are found in naturally occurring $$\hbox {Cu}_2\hbox {O}$$ Cu 2 O . However, for technological applications, the ability to grow high-quality synthetic samples is essential. The fabrication of thin-film $$\hbox {Cu}{}_2\hbox {O}$$ Cu 2 O samples is of particular interest as they hold potential for observing extreme single-photon nonlinearities through the Rydberg blockade. Nevertheless, due to the susceptibility of high-lying states to charged impurities, growing synthetic samples of sufficient quality poses a substantial challenge. This study successfully demonstrates the CMOS-compatible synthesis of a $$\hbox {Cu}{}_2\hbox {O}$$ Cu 2 O thin film on a transparent substrate that showcases Rydberg excitons up to $$n = 8$$ n = 8 which is readily suitable for photonic device fabrications. These findings mark a significant advancement towards the realization of scalable and on-chip integrable Rydberg quantum technologies.